STATUS OF AN UZBEK LANGUAGE. NATIONAL LITERATURE OF UZBEKISTAN AND ITS REPRESENTATIVES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract examines the historical significance and contemporary relevance of the Uzbek language and its national literature within the cultural context of Uzbekistan. The Uzbek language, rooted in Turkic linguistic traditions with influences from Persian and Arabic, has evolved over centuries, culminating in its modern status as the official language of Uzbekistan. The narrative delves into the rich literary heritage of Uzbekistan, highlighting pivotal figures such as Alisher Navoi and Babur, who laid the foundation for Uzbek literature during the Timurid dynasty. The discussion progresses to the modern era, exploring the works of Abdulla Qahhar, Choʻlpon, and Hamid Alimjan, who contributed significantly to the development of contemporary Uzbek literature. Contemporary Uzbek literature, represented by writers like Hamid Ismailov and Dilfuza Iskhakova, addresses universal themes while reflecting on issues of identity, tradition, and modernity. The transition from Cyrillic to Latin script underscores efforts to preserve cultural identity and engage with global literary trends. Challenges facing Uzbek literature, including technological disruptions and political constraints, are considered alongside opportunities for growth, such as translation initiatives and literary festivals. Ultimately, Uzbek literature emerges as a dynamic and resilient expression of Uzbekistan's cultural identity, fostering connections with global audiences while celebrating its linguistic and literary heritage.